Deposition and Determination of Band Alignment of Al2O3/Si Gate Stacks by New CVD Chemistry - He, Gang; Zhang, Jiwen; Chen, Xuefei; Deng, Bin; Song, Xueping; Sun, Zhaoqi (Asian Journal of Chemistry, 2014)
Compared to other precursors, dimethyl aluminum hydride [(CH3)2AlH] has high vapor pressure of 2 torr at room temperature and a potential to form alumina films by CVD/ALD with low carbon impurity. Additionally, low deposition temperature of dimethyl aluminum hydride will avoid the formation of low-k interfacial layer during deposition, which is suitable for the MOS device fabrication. In this study, Al2O3 thin films have been deposited successfully from dimethyl aluminum hydride and O2 to investigate the MOCVD behaviour as well as the observation of the band alignment of deposited Al2O3/Si gate stacks.